2016
DOI: 10.1055/s-0036-1583547
|View full text |Cite
|
Sign up to set email alerts
|

The Next 10 Years in Voice Evaluation and Treatment

Abstract: Voice disorders are thought to affect approximately one third of all individuals within the United States during their lifetime. Individuals who require the use of their voice as part of their occupations are at highest risk for developing voice problems. Unfortunately, efficient diagnosis and effective management of voice disorders can be challenged by difficulty accessing professionals with the necessary expertise to diagnose and treat voice problems efficiently. Within the next decade, technological advance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 66 publications
0
2
0
1
Order By: Relevance
“…It is anticipated that the examination of laryngeal endoscopic images will allow early detection of pathologies [5]. Vocal folds, as the main functional organ within the larynx, are sensitive structures for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…It is anticipated that the examination of laryngeal endoscopic images will allow early detection of pathologies [5]. Vocal folds, as the main functional organ within the larynx, are sensitive structures for surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Udowodniono, że nawet krótkie szkolenia teoretyczne oraz ambulatoryjne kursy emisji głosu w połączeniu z fizjoterapią i psychoterapią wpływają na poprawę parametrów głosu. W warunkach codziennego, kilkugodzinnego obciążenia wysiłkiem leczenie zaburzeń głosu nie jest jednak łatwe [5,6].…”
Section: Wstępunclassified
“…The effectiveness of complex voice rehabilitation programs in ambulatory care has been assessed by many authors [12][13][14][15]. It was observed that vocal hygiene training significantly improves voice quality and reduces disorder symptoms [16,17]. Multicenter efforts to improve quality of care for persons professionally and strenuously using their voice resulted in the development of an interdisciplinary 24-day vocal prophylactic and rehabilitation program conducted in health resort hospitals [18].…”
Section: Introductionmentioning
confidence: 99%